Horizontal Vibrations of Embedded Foundation in Multi-Layered Poroelastic Soils - Teerapong Senjuntichai (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
In this paper, the dynamic response of rigid foundations of arbitrary shape embedded in multi-layered poroelastic soils subjected to time-harmonic horizontal loading is presented. The soil-structure interaction problem is investigated by employing a discretization technique and flexibility equations based on the influence functions obtained from an exact stiffness matrix scheme. The present solution scheme is verified with relevant existing solutions of rigid foundations on homogeneous elastic and poroelastic media. A selected set of numerical results are illustrated to portray the influence of various parameters, namely, frequency of excitation, poroelastic material parameters, foundation shapes, embedded depth, and the supporting soil systems, on non-dimensional horizontal compliances of rigid foundations.